Synthesis of poly(alkylaniline)s by aqueous chemical oxidative polymerization and their use as stimuli-responsive liquid marble stabilizer. (6th January 2021) - Uda, Makoto; Higashimoto, Shinya; Hirai, Tomoyasu; Nakamura, Yoshinobu; Fujii, Syuji
Abstract: Poly(alkylaniline) grains with several tens micrometer-sized diameter were successfully synthesized by aqueous chemical oxidative polymerization. The grains were aggregates consisting of submicrometer sized-atypical particles, which was confirmed by scanning electron microscopy studies. Static contact angle measurements of water droplets on the compressed pellets of the grains indicated that the hydrophobicity increased with an increase of alkyl group length and the alkyl groups bonded to phenyl ring is expected to be exposed to air phase. The data obtained through thermography indicated the grains showed near infrared light-to-heat photothermal property. The dried grains could work as an effective liquid marble stabilizer by efficient adsorption to air-water interface. The remote locomotion control of liquid marble could be attained by near-infrared light-induced Marangoni flow. Furthermore, the liquid marbles could detect oil contamination on water surface by disruption. Graphical abstract: Synthesis of poly(alkylaniline) grains as a stimuli-responsive liquid marble stabilizer by aqueous chemical oxidative polymerization. Image 1 Highlights: Poly(alkylaniline) grains were synthesized by aqueous chemical oxidative polymerization. Poly(alkylaniline) grains functioned as a liquid marble stabilizer. Light irradiation induced locomotion of liquid marble due to Marangoni propulsion. Liquid marble could detect oil contamination on water surface.